Internet of things-based floor cleaning robot - Abdul Hafiz Kassim; Mohamad Yusof Mat Zain; Mohd Abdul Talib Mat Yusoh; Mohd Nazrul Sidek; Raja Mohd Noorhafizi Raja Daud; Ahmad Izzat Mod Arifin; Mazratul Firdaus Mohd Zin (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Internet of t hings (IoT) based floor cleaning robot (FC - Rob) is a floor cleaning robot that uses a smartphone to assist users, primarily housewives and mothers, in completing their chores. The NodeMCU ESP8266 serves as the robot’ s “brain” and is controlled by a smartphone application for the purpose of this research. In accordance with current trends, a n iOS and Android application using Blynk has also been developed for users to control the robot’ s movements, making it the ideal solution for time - crunched individuals. FC - Rob is propelled by two d irect current (DC) motors to ensure comprehensive floor cl eaning. The results of this research are strengthened by tests conducted on battery life and two types of fabric, as well as a comparison with two types of commercially available robots. The positive findings of these tests on this robot demonstrate its effectiveness and efficiency in cleani ng houses, as well as its reasonable cost and educational value for children.